Student Quality and Evaluation of Entrepreneurship Education in Kedah Zakat School: A Case Study of Maahad Dini Kedah Zakat School - Anuar, Abdul Rahim; Mohd Khan, Shazida Jan; Mohd Saad, Nariman; Osman, Azim Azuan (The Mattingley Publishing Co., Inc., 2020)
Education is one of the means to address the problem of poverty among poor households especially by providing access to education for children whose parents are poor or in the context of Zakat, as the beneficiary (asnaf). Social mobility through education will lift their families out of the inter-generation poverty trap. Thus, the Kedah State Zakat Board (LZNK) established the first Kedah Zakat School (KZS), the Maahad Dini KZS in Alor Setar in January 2018 and followed by the Pondok Moden Zakat Kedah (PMZK) in Sungai Petani in March 2018. The objective of the study is to assess the impact of KZS on students’ self-efficacy, self-confidence, leadership qualities, and entrepreneurship. This study employs PLS-SEM based on a census survey with a sample size of 50 (N = 50). The findings show that student self-confidence and student self-efficacy has a positive sign towards entrepreneurship intention. The findings also indicate that the schools teaching delivery need more improvement as the study reveals a contrast result. Further, the role of co-op activities involvement is negatively moderated on the relationship between school teaching delivery and entrepreneurial intention. As for the future improvement of the KZS, the education curriculum needs to be market-oriented so that students have the skills to meet the market demand. This can increase their social mobility and address the inter-generation poverty trap.